Observation of the decay B+ -> psi(2S)phi(1020)K+ in pp collisions at root s=8 TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Ero, J.; Flechl, M.; Friedl, M.; et al. (My University, 2017)
The decay B+ -> psi(2S) phi(1020) K+ is observed for the first time using data collected from pp collisions at root S = 8 TeV by the CMS experiment at the LHC, corresponding to an integrated luminosity of 19.6 fb(-1). The branching fraction of this decay is measured, using the mode B+ -> psi(2S) K+ as normalization, to be (4.0 +/- 0.4 (stat)+/- 0.6 (syst)+/- 0.2 (B)) x 10(-6), where the third uncertainty is from the measured branching fraction of the normalization channel. (C) 2016 The Author(s). Published by Elsevier B.V.
Citation: Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., . . . Collaboration, C. M. S. (2017). Observation of the decay B+ -> psi(2S)phi(1020)K+ in pp collisions at root s=8 TeV. Physics Letters B, 764, 66-86. doi:10.1016/j.physletb.2016.11.001
Keywords: Cms; Physics; B Physics; Rare B Decays; Astronomy & Astrophysics; Physics